INTERACTIVE METHODS AND THEIR CHARACTERISTICS IN THE CREDIT MODULE SYSTEM - Gauhar Serikbayevna Haldarchaeva (Western European Studies, 2024)
In the article, an analysis was carried out to verify the editorial and psychological possibilities of improving the technology of developing students' foreign language skills in the process of independent education and to modernize the modern foreign language education in the conditions of the credit-module system
Keywords: Interactive; communication; communicative